2002
DOI: 10.1207/153248302760179129
|View full text |Cite
|
Sign up to set email alerts
|

Politics and Basking-in-Reflected-Glory: A Field Study in Flanders

Abstract: This field study tested whether the basking-in-reflected-glory phenomenon would emerge in a political context. Two days before the general elections in Flanders (Belgium), 3 urban regions were systematically surveyed by 10 observers. These observers unobtrusively registered the addresses of private houses that displayed at least 1 poster (N = 482) or 1 removable lawn sign (N = 180) supporting a political party. The day after the elections, the observers checked whether the registered houses still displayed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 8 publications
4
20
1
Order By: Relevance
“…The literature on ''basking in reflected glory'' (BIRGing) supports this idea. For instance, individuals are more likely to cognitively and publicly associate with a third party when that group has just won an athletic contest (Cialdini et al, 1976) or political victory (Boen et al, 2002). While this pattern has not been applied to media quality in the past, it could be inferred that as the quality of the media increases, audience members will be more likely to identify with the creators of the media as a way of improving their own self-esteem.…”
Section: Message Quality and Identificationmentioning
confidence: 99%
“…The literature on ''basking in reflected glory'' (BIRGing) supports this idea. For instance, individuals are more likely to cognitively and publicly associate with a third party when that group has just won an athletic contest (Cialdini et al, 1976) or political victory (Boen et al, 2002). While this pattern has not been applied to media quality in the past, it could be inferred that as the quality of the media increases, audience members will be more likely to identify with the creators of the media as a way of improving their own self-esteem.…”
Section: Message Quality and Identificationmentioning
confidence: 99%
“…Elsbach and Bhattacharya (2001) found that members of the National Rifle Association (NRA) who perceived that the NRA's reputation would be poor were inclined to separate themselves from the NRA. Along similar lines, Boen et al (2002) revealed that people tend to avoid being perceived as a supporter of defeated parties after a political election. The same logic applies to organizations that avoid being evaluated in the same league with less reputable others.…”
Section: Theory and Hypothesesmentioning
confidence: 81%
“…Competitive comparison is one type of social comparison. According to social comparison theory, a comparison between two actors can be viewed as an affiliation (see Buunk and Gibbons, 2007) through which the two actors being compared are considered to be in the same league (Boen et al , 2002; Snyder, Higgins, and Stucky, 1983). 2 Following this logic, competitive comparison, depending on the targets of the comparisons, can create an opportunity for a focal firm to manage its public image and achieve market success.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The desire to be associated with success can play an important role in leadership. Boen et al (2002) observed that individuals will keep lawn signs out longer for political candidates. Bernherdt, Dabbs, Fielden & Lutter, (1998) found an increase in testosterone levels among men when affiliated teams were winning games.…”
Section: Resultsmentioning
confidence: 99%